Relationship between Certification and Improving the Quality of Teaching Lecturers at the Al-Amin Dompu Teaching and Education College (STKIP) - Yeni Rahamawati; Nur Islamiati; Baharudin Baharudin (JURNAL PENDIDIKAN IPS, 2023)
This research is motivated by the fact that there are still problems faced by tertiary institutions, namely one of them is the lack of motivation from lecturers in their duties contained in the Tridharma and other important factors that affect lecturer performance include professionalism such as lecturer professional allowances or lecturer certification. This study aims to find out how the relationship between lecturer certification and the teaching quality of lecturers at STKIP Al Amin Dompu. The approach used in this study is a quantitative correlation approach with the type of ex-post facto. The research population is all lecturers at STKIP Al Amin Dompu. The sampling technique used random sampling which totaled 28 lecturers. Data collection techniques using a questionnaire. The data analysis technique used the product moment correlation test with SPSS type 29.00 for windows. The results of the study showed that there was a significant relationship between the two variables, namely lecturer certification and the teaching quality of lecturers at STKIP Al Amin Dompu. This can be seen from the significance value which is smaller than the significance level value or 0.01 <5% (0.05). In addition, the results obtained r count > r table of 0.533 > 0.361. Which shows a strong relationship between the two variables. This research is expected to become the view that lecturer certification is a factor to motivate lecturers in carrying out the tridharma but not to be a benchmark for lecturers in improving lecturer abilities, especially in teaching abilities.